Anthropometric features and functional state of the cardiovascular system in qualified athletes of various sports - N. P. Garganeeva; I. F. Taminova; V. V. Kalyuzhin; E. V. Kalyuzhina; I. N. Smirnova; T. V. Sarycheva (Российский кардиологический журнал)
Aim. To assess the anthropometric characteristics and functional state of the cardiovascular system in qualified athletes of various sports.Material and methods. A total of 136 male athletes were examined. Qualified athletes (n=116) (age, 22,07±4,10 years, sports experience 9,56±3,08 years) were divided into groups: I (n=30) — wrestling, judo, II (n=27) — cross-country skiing, biathlon, III (n=33) — powerlifting, IV (n=26) — volleyball. Control group (n=20) consisted of those training less than 3 years. We performed anthropometry with assessment of body height and weight, chest circumference, body surface area, body mass index (BMI), Pignet index, Erisman index, grip and back strength test. Echocardiography, cycle ergometry with assessment of physical working capacity (PWC170) and maximum oxygen consumption (MOC). The relationship between traits was assessed using the Spearman rank correlation coefficient (rs). Critical significance level was p=0,05.Results. According to echocardiography, qualified athletes had significant differences in structural parameters. Group II was characterized by an increase in left ventricular (LV) volumetric dimensions and identified correlations of BMI and body surface area with end-diastolic dimension (r=0,602), end-diastolic volume (r=0,591), end-systolic volume (ESV) (r=0,429), stroke volume (r=0,597), PWC170 (r=0,550). Groups I and III were characterized by an increase in LV posterior wall (LVPWT) and interventricular septal (IVST) thickness. In group I, there was a relationship between body surface area and LVPWT (r=0,413); Pignet index with MOC (r=0,623); PWC170 with Erisman index (r=0,573), strength of the right (r=0,610) and left hand (r=0,515), back muscles (r=0,445). Group III had the highest BMI and body surface area, while relationships were identified with LVPWT (r=0,426), IVST (r=0,409), LV mass (LVM) (r=0,453), and back muscle strength (r=0,464); the Erisman index correlated with LVM index (r=0,359). In group IV, the parameters of height, body weight and body surface area are interrelated with LVM (r=0,731), LVPWT (r=0,523), IVST (r=0,399), ESV (r=0,504), end-systolic dimension (r=0,467), right hand strength (r=0,583).Conclusion. The relationships established by correlation analysis showed that anthropometric features are important components and criteria for assessing cardiac hemodynamics function in qualified athletes, depending on the type of sport and the duration of training, which must be taken into account when achieving sports results.